2007
DOI: 10.1093/nar/gkm916
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the role of ribonucleases in Salmonella small RNA decay

Abstract: In pathogenic bacteria, a large number of sRNAs coordinate adaptation to stress and expression of virulence genes. To better understand the turnover of regulatory sRNAs in the model pathogen, Salmonella typhimurium, we have constructed mutants for several ribonucleases (RNase E, RNase G, RNase III, PNPase) and Poly(A) Polymerase I. The expression profiles of four sRNAs conserved among many enterobacteria, CsrB, CsrC, MicA and SraL, were analysed and the processing and stability of these sRNAs was studied in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
169
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(181 citation statements)
references
References 88 publications
(129 reference statements)
9
169
1
2
Order By: Relevance
“…It is known for some sRNAs that their turn-over is catalyzed by the endoribunucleases E or III. [23][24][25] Base pairing to the target RNA (B) stability determination of Oxys sRNA in strain lacking pNpase-RNase II (sK5726) and in a strain lacking pNpase-RNase II-RNase e ts (SK5704) and the isogenic wild type background MG1693. OxyS RNA half-lives were calculated from at least 3 independent biological repeats and the standard deviation is given.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known for some sRNAs that their turn-over is catalyzed by the endoribunucleases E or III. [23][24][25] Base pairing to the target RNA (B) stability determination of Oxys sRNA in strain lacking pNpase-RNase II (sK5726) and in a strain lacking pNpase-RNase II-RNase e ts (SK5704) and the isogenic wild type background MG1693. OxyS RNA half-lives were calculated from at least 3 independent biological repeats and the standard deviation is given.…”
Section: Resultsmentioning
confidence: 99%
“…We also analyzed strains lacking the RNA binding protein Hfq, which is known to affect RNA stability. 22,23 Since we found that DsrA is also expressed at high levels in the presence of hydrogen peroxide and we considered an influence of DsrA on OxyS stability, we also constructed and analyzed mutants lacking DsrA. Our data reveal a complex interplay of the different RNases, Hfq and DsrA in OxyS processing, which is strongly dependent on growth phase.…”
mentioning
confidence: 96%
“…The oligonucleotides used for disruption (labeled ''UP'' and ''DO'') are listed in supporting information, Table S1, together with the oligonucleotides (labeled ''E'') used for allele verification by the polymerase chain reaction. Disruption of the rne gene, which encodes ribonuclease E, was performed with primers that eliminate the C-terminal region (Viegas et al 2007). For the construction of transcriptional and translational lac fusions in the Salmonella chromosome, FRT sites generated by excision of Km r cassettes (Datsenko and Wanner 2000) were used to integrate either plasmid pCE37 or pCE40 (Ellermeier et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Ribonuclease E had been previously described as a SPI-1 regulator (Fahlen et al 2000). For construction of an Rne À mutant, only a portion at the 39 end of the rne coding sequence was eliminated (Viegas et al 2007). Analysis of hilD mRNA content was performed in two sets of experiments.…”
Section: Levels Of the Spi-1 Transcription Factorsmentioning
confidence: 99%
“…CTIG270 may be playing a role in the lack of bacterial cell division. C. trachomatis, although lacking Hfq and RNase E, encodes a homolog of RNase III which, among other functions, can degrade dsRNA (Viegas et al, 2007). To test this phenomenon we may need to genetically control the expression of ftsI inside Chlamydia and measure the effect on CTIG270 transcript half life at various time points.…”
Section: Expression Of Ctig270 During Stress Conditionsmentioning
confidence: 99%